Technology-Based Responses to Technology-Facilitated Domestic and Family Violence: An Overview of the Limits and Possibilities of Tech-Based "Solutions". (March 2023) - Harkin, Diarmaid; Merkel, Robert
It is increasingly common for domestic and family violence to have an element of technology-facilitated abuse (TFA). As a result, technology-based responses have emerged to address TFA. Using observations from several empirical research projects into TFA, it will be shown that technology-based responses are necessary without being sufficient, and that they have persistent limitations that need to be recognized. Relatedly, it will be argued that there should be an ongoing emphasis on the development of human resources as a support for those experiencing TFA, particularly the use of professional DV support workers.